2017
DOI: 10.13031/trans.12156
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Study of Odor from Pig Buildings to Improve Understanding of Biotrickling Filter Performance

Abstract: Abstract. Recently, bioreactors, such as biotrickling filters, have been used to reduce odor and gas emissions from livestock facilities. Considerable efforts have already been made over the years to evaluate and improve the efficiencies of bioreactors used for this purpose; however, no study has yet been published that attempts to provide a thorough assessment of the performance of bioreactors in eliminating most (if not all) of the gases exhausted from swine facilities. Thus, this study was conducted to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The swine manure is the principal cause of odor derived from swine farms [ 11 ]. In addition, main factor affecting the composition of swine manure was reported to be the feed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The swine manure is the principal cause of odor derived from swine farms [ 11 ]. In addition, main factor affecting the composition of swine manure was reported to be the feed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…BTFs have some advantages over biofilters using organic materials as filter bed, allowing a better control of operational parameters, like pH and temperature, and a better control of nutrients supply and by‐products accumulation. Several authors have reported the feasibility of using BTFs for treating different odorous gaseous emissions: sewage systems, 9 animal production buildings, 10 composting processes, 11 and animal waste treatment facilities 12 . The potentialities of biological processes for the treatment of odorous emissions from rendering operations have also been highlighted by a few authors, considering mainly biofilters 13–15 …”
Section: Introductionmentioning
confidence: 99%
“…In the agricultural sector, offensive odors are mainly generated by the incomplete anaerobic decomposition of manure and by manure management (storage, handling and land application) [6]. Ammonia (NH 3 ), hydrogen sulphide (H 2 S) and volatile organic compounds (VOCs) are the principal odorous substances emitted by pig farms [7].…”
Section: Introductionmentioning
confidence: 99%